The patient burden of nocturnal polyuria in the United States: Results from the epidemiology of nocturnal polyuria (EpiNP) study. Issue 3 (19th January 2023) - Chapple, Christopher R.; Rosenberg, Matt T.; Mueller, Elizabeth R.; Chughtai, Bilal; Weiss, Jeffrey P.; Juul, Kristian; Brooks, Anne B.; Bacci, Elizabeth D.; Andersson, Fredrik L.; Coyne, Karin S.; Bosch, JLH Ruud
Abstract: Objectives: To explore the impact of nocturnal polyuria (NP) on health‐related quality of life (HRQoL), work productivity, mental health, fatigue, bother, and daytime sleepiness. Materials and Methods: This large‐scale, US population‐representative epidemiologic study was conducted in two parts: a web‐based survey and 3‐day bladder diary. Consenting participants completed the baseline Epidemiology of NP (EpiNP) survey online (Lower Urinary Tract Symptoms [LUTS] Tool, comorbidities, burden, and multiple HRQoL measures). Participants who reported ≥2 voids/night, and a random sample of 100 respondents each reporting 0 or 1 void/night, were sent urine measurement containers and asked to complete the 3‐day bladder diary. NP was defined as Nocturnal Polyuria Index >0.33 (NPI33) or nocturnal urine production >90 ml/h (NUP90). Five subgroups were created: Idiopathic NP (NP with no underlying cause), NP associated with symptoms of overactive bladder (NPOAB) or bladder outlet obstruction (NPBOO; men only), NP associated with other comorbidities (NPCOM; e.g., diabetes, hypertension, heart disease, sleep apnea), and no NP (did not meet NP criteria). Results: A total of 4893 men and 5297 women completed the EpiNP survey; mean age was 54.4 ( SD  = 14.7). Significantly greater patient burden ( p  < 0.0001) was evidenced in the nocturia group (≥2 voids/night) versus no nocturia group (0–1 void/night) on daily impact of nocturia, LUTS Bother, prostate symptoms (men only), work productivity, physical and mental health component scores, depression, fatigue, and daytime sleepiness. NP subgroup analyses showed men in the NPBOO group and women in the NPOAB group reported the greatest impact on LUTS bother, fatigue, physical health, work productivity impairment, daytime sleepiness, and depression (women only). Conclusion: This was the first large‐scale, epidemiologic study to explore the impact of different forms of NP on patients' HRQoL. Findings demonstrate that NP associated with other urologic or comorbid conditions appears to have greater patient burden than idiopathic NP, in particular for women.